Reaching for the stars knowledge transfer at PolyU (Hong Kong, 2009)
This book introduce about an underdog overtakes, driven to succeed, centres of excelence. IP policy and the importance of protection, seeding entrepreneurs, how innovative marketing leads to commercialization...
Keywords: Đối tác chuyển giao tri thức,Knowledge transfer partnerships